Trust Building, Diagnosis, and Repair in the Context of Negotiation - FERRIN, Donald Lee (Institutional Knowledge at Singapore Management University, 2014)
In this chapter, the authors summarise the empirical research on trust and discuss how it can be put into practice to effectively diagnose, build and repair trust in the context of negotiations.